2003
DOI: 10.1183/09031936.03.00057803
|View full text |Cite
|
Sign up to set email alerts
|

Formoterol protects against platelet-activating factor-induced effects in asthma

Abstract: Platelet-activating factor (PAF) is an inflammatory mediator that provokes neutropaenia, bronchoconstriction and gas exchange defects due to exudation of bulk plasma within the airways. While the inhibitory effects of short-acting b 2 -agonists on PAF-induced disturbances have been consistently shown, those of longacting b 2 -agonists are less convincing.To further explore the mechanisms involved in PAF challenge in asthma, 12 patients (forced expiratory volume in one second, 90¡4% predicted) were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…PAF is an endogenous lipid mediator with mitogenic properties [37] and has been reported to aggravate asthmatic conditions [38, 39]. We found that S -albuterol, but neither racemic albuterol nor levalbuterol, induced the expression of PAF receptor protein by the smooth muscle cells.…”
Section: Discussionsupporting
confidence: 57%
“…PAF is an endogenous lipid mediator with mitogenic properties [37] and has been reported to aggravate asthmatic conditions [38, 39]. We found that S -albuterol, but neither racemic albuterol nor levalbuterol, induced the expression of PAF receptor protein by the smooth muscle cells.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, we found that activation of the PAF-receptor-mediated signaling pathway may be one mechanism by which (S) -albuterol induces HBSMC proliferation. PAF is an endogenous lipid mediator with mitogenic properties [40, 41], and has been reported to aggravate asthmatic conditions [42,43,44,45]. In our study, the specific PAF receptor antagonist CV-3988, at a low concentration of 1 µ M , inhibited (S) -albuterol-induced cell growth, but neither reversed levalbuterol-induced inhibition of cell growth, nor produced additive inhibition with levalbuterol.…”
Section: Discussionmentioning
confidence: 65%
“…Platelet‐activating factor (PAF; 1‐ O ‐alkyl‐2‐acetyl‐ sn ‐glycero‐3‐phosphocoline) is a potent proinflammatory mediator implicated in angiogenesis, atherosclerosis, anaphylaxis, and endotoxemia 7,8 . PAF is also involved in a variety of lung functions, such as airway and vascular tone, ciliary beating frequency, and endothelial permeability, resulting in gas exchange impairment 9,10 . In horse airways, PAF participates in the pathophysiology of recurrent airway obstruction (RAO), leading to an increased recruitment and activation of neutrophils and eosinophils in the lung, as well as disturbances in the respiratory function 11 …”
mentioning
confidence: 99%
“…7,8 PAF is also involved in a variety of lung functions, such as airway and vascular tone, ciliary beating frequency, and endothelial permeability, resulting in gas exchange impairment. 9,10 In horse airways, PAF participates in the pathophysiology of recurrent airway obstruction (RAO), leading to an increased recruitment and activation of neutrophils and eosinophils in the lung, as well as disturbances in the respiratory function. 11 RAO is closely related to environmental factors, 12,13 but the contribution of the different environmental and stable factors, as etiological components of the airway inflammation of young athletic horses, awaits clarification.…”
mentioning
confidence: 99%